Differences in maternal temperature during labour with remifentanil patient-controlled analgesia or epidural analgesia: a randomised controlled trial. Issue 4 (November 2015) - Douma, M.R.; Stienstra, R.; Middeldorp, J.M.; Arbous, M.S.; Dahan, A.
Highlights We compared side effects of epidural analgesia with remifentanil patient-controlled analgesia during labour. Epidural analgesia was associated with a higher incidence of maternal temperatures ⩾38°C. Remifentanil resulted in more frequent and deeper hypoxaemic events. Remifentanil resulted in more sedation and nausea. Epidural analgesia provides better analgesia compared to remifentanil.